Civil Liability of Businesses for The Loss of Consumer Goods Delivery Packages Through Land Transportation Services (Study at PT. Antar Lintas Sumatra Medan) - Djodie, Mohammad Effan; Jamillah; Marsella (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2024)
Transportation is a field of activity that is very important in the life of the Indonesian people. With that the Government established a Law no. 8 of 1999 which stated that "Consumer protection is all efforts that guarantee legal certainty to provide protection to consumers". This is to find out how the company PT. Antar Lintas Sumatra responds to consumers who lose goods in using the transportation services of PT. Antar Lintas Sumatra. The formulation of the problem in research at PT. Antar Lintas Sumatra includes how the company’s responsibilities, settlement mechanisms and how the company solving problems in civil liability. This research is an normative juridical law research. The study uses secondary data and primary data. The transportation service provider company PT. Antar Lintas Sumatra makes agreements and agreements with consumers in the form of agreements in using PT. Antar Lintas Sumatra’s transportation. Because consumer protection is closely related to legal protection, consumers are entitled to protection in the form of company responsibility if there is legal protection. Consumer protection covers various aspects of the law relating to the protected material, not just physical protection. There is no imbalance in disputes in an agreement because there is an agreement at the beginning between the customer and the transportation provider.